Analisis Adopsi dan Penggunaan Aplikasi Pertanian Digital oleh Petani Skala Kecil di Kabupaten Tuban dengan Model UTAUT - Sihombing, Maruli Tua; Hubeis, Musa; Cahyadi, Eko Ruddy (Institut Pertanian Bogor, 2024)
The agricultural sector, as the cornerstone of food security in Indonesia, is predominantly managed by smallholder farmers who are still accustomed to conventional methods. The challenges of climate change will affect the upstream agricultural industry, necessitating farmers to digitally transform their operations to enhance productivity. Digital-based agricultural applications have been introduced by several technology service developers to farmers, but their adoption rates are still relatively low. One common model used to study the acceptance and use of technology is the Unified Theory of Acceptance and Use of Technology (UTAUT). The UTAUT model has not been widely applied in Indonesia, specifically among smallholder farmers with specific characteristics. This research aims to analyze the factors influencing the intention and behavior of smallholder farmers to adopt and use digital agricultural application technology using the UTAUT model. The research was conducted from March to April 2024 in the agricultural hub region of Tuban Regency, with 124 smallholder farmers as respondents, using purposive sampling technique. This research utilized a descriptive data analysis method based on cross-tabulation with an SEM-PLS approach. The findings indicate that performance expectations, effort expectations, and facilitation conditions collectively influence the behavior of using digital agricultural applications through farmers' behavioral intentions. Differences in age levels were found to moderate the relationship among variables. Younger farmers need to be fully engaged in utilizing the dissemination of digital agricultural application technology through training practices supported by improved facilities